2019
DOI: 10.5603/arm.a2019.0002
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Dysfunction in Children with Clinically Stable and Exacerbated Asthma

Abstract: Introduction: In children with asthma, endothelial dysfunction signs are observed, and their extent depends on the severity of the disease. These changes are also present in remission. High level of soluble Vascular Cell Adhesion Molecule-1 (sVCAM-1) expression causes active adhesion of inflammatory cells and can indicate direct endothelium participation in development and supporting of chronic inflammation. Bronchial asthma (BA) is characterised by airways chronic inflammation. A special role in this inflamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Accumulating evidence suggests that low-grade chronic systemic inflammation and autoimmune diseases are risk factors for cardiovascular disease (CVD). Several studies have shown an increased risk of CVD in patients with asthma [ 2 , 3 , 4 , 5 ], chronic obstructive pulmonary disease (COPD) [ 6 , 7 , 8 , 9 , 10 ], cystic fibrosis (CF) [ 11 , 12 , 13 , 14 ], alpha1-antitrypsin deficiency [ 15 , 16 ], and obstructive sleep apnea [ 17 ]. For improved prognosis and to prevent amplifying CVD, understanding the association between pulmonary diseases and CVD has important implications for disease management and targeted treatments.…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating evidence suggests that low-grade chronic systemic inflammation and autoimmune diseases are risk factors for cardiovascular disease (CVD). Several studies have shown an increased risk of CVD in patients with asthma [ 2 , 3 , 4 , 5 ], chronic obstructive pulmonary disease (COPD) [ 6 , 7 , 8 , 9 , 10 ], cystic fibrosis (CF) [ 11 , 12 , 13 , 14 ], alpha1-antitrypsin deficiency [ 15 , 16 ], and obstructive sleep apnea [ 17 ]. For improved prognosis and to prevent amplifying CVD, understanding the association between pulmonary diseases and CVD has important implications for disease management and targeted treatments.…”
Section: Introductionmentioning
confidence: 99%
“…Quality of life is an important indicator to evaluate the effectiveness of postoperative pulmonary rehabilitation, and is also one of the ultimate indicators of clinical rehabilitation treatment, covering 5 aspects including physical health, mental health, social function, daily life activities and good sense of self. The quality of life scale (EORTC-QLQ-C30) and the Lung Cancer Specific Scale (EORTC-QLQ-LC13) of the European Organization for Research and Treatment of Cancer (EORTC) can be used to evaluate the quality of life [46].…”
Section: Subjective Effect Evaluation 421 Quality Of Life Evaluationmentioning
confidence: 99%
“…In asthma and COPD, endothelial dysfunction, along with vessel inflammation, has been observed (Green and Turner, 2017). Moreover, in asthmatic children, the extent of endothelial dysfunction, as manifested by excess production of circulating vascular cell adhesion molecule-1 (sVCAM-I), was found to be associated with asthma severity (Butov et al, 2019), indicating the critical role of ECs in asthma pathogenesis. Indeed, in light that ECs serves as the gateway of inflammatory cells' transendothelial migration into the lung parenchyma, the activation of ECs, e.g., expression of adhesion molecules and pro-inflammatory mediators, would be crucial in modulating inflammatory cell recruitment.…”
Section: Endothelial Cellsmentioning
confidence: 99%